Genital warts: comparing clinical findings to dermatoscopic aspects, in vivo reflectance confocal features and histopathologic exam - John Verrinder Veasey; Valeria Maria de Souza Framil; Sidney Roberto Nadal; Alessandra Cristine Marta; Rute Facchini Lellis (Sociedade Brasileira de Dermatologia, 2014)
Genital warts can be diagnosed through physical examination and confirmed by histopathology. Noninvasive methods are useful for ruling out other diagnoses with no harm to the patient. In this study the clinical findings were compared to dermoscopy, reflectance confocal microscopy (RCM), and to histopathology findings, in order to determine possible patterns that can aid diagnosis of the lesion. It was possible to identify structural changes on reflectance confocal microscopy that are already known by dermoscopy, in addition to cellular changes previously seen only by histopathological examination. This study shows the use of reflectance confocal microscopy in cases of genital warts, providing important information that can be used in further studies.